Ángel Emilio Hidalgo, Guayaquil. Los diez-los veinte. Fotografías de José Rodríguez González, Enrique de Grau, Miguel Ángel Santos y Rodolfo Peña Echaiz, Quito, Consejo Nacional de Cultura, 2009, 101 pp. - Cabrera Hanna, Santiago (Procesos. Revista Ecuatoriana de Historia, 2015)
s.r